The English Competencies of Tourism High School Students - Nurika, Intan Fajrian; Engelbrecht, Natasha; Zemieche, Amina (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This study was designed to investigate what are the competencies of tourism high school students in DKI Jakarta. Methodology: There were 420 students of 21 tourism high schools in DKI Jakarta that participated in this study. Theoretical (study of theoretical literature and sources) and empirical methods of the research data obtaining methods (students and teachers’ interviews, teachers and students questionnaire, and unstructured observation) and also both qualitative and quantitative data processing method were used in this study. Main Findings: The result showed that the most needed skill to work in tourism industries is speaking skill. Students were expected to have good oral communication since it was useful when they had a job training program in real industry. They need more vocabularies which are in tourism terminology. However, the result of teachers’ instruments indicated more than 75% English teachers focus on national examination which is mean that students learned more in reading rather than speaking. Teachers also followed a curriculum which is provided for all major of vocational high school. The curriculum compilers were not develop curriculum for each major. It means that the curriculum itself was in general ideas. The teachers should select and develop the appropriate materials for students’ major. Novelty/Originality of this study: It can be concluded that the tourism high school students need good oral communication by improving speaking and also listening skill to achieve both learning objective stated in Regulation Number 22 year 2006 and industry needs.